Efficacy and safety of vilaprisan in women with uterine fibroids: Data from the phase 2b randomized controlled trial ASTEROID 2. (September 2020) - Gemzell-Danielsson, Kristina; Heikinheimo, Oskari; Zatik, Janos; Poka, Robert; Rechberger, Tomasz; Hudecek, Robert; Petersdorf, Kathrin; Ramirez, Francisco; Faustmann, Thomas; Groettrup-Wolfers, Esther; Seitz, Christian
Highlights: Vilaprisan, a selective progesterone receptor modulator (SPRM), is a potential treatment for uterine fibroids (UF). In women with UF, vilaprisan 2 mg daily induced amenorrhea after 12 weeks. Vilaprisan controlled heavy menstrual bleeding (HMB) and decreased UF volume. After 12 weeks of vilaprisan treatment, no safety concerns were identified. Abstract: Objective: To assess the efficacy of vilaprisan compared with placebo in the management of the symptoms of uterine fibroids (UF), with a secondary objective to provide a descriptive comparison with ulipristal acetate. Study design: The randomized, parallel-group, double-blind, placebo- and active-controlled, multicenter ASTEROID 2 trial assessed the efficacy and safety of vilaprisan versus placebo and ulipristal acetate for two 12-week treatment periods in women with ≥1 UF experiencing heavy menstrual bleeding (HMB). The primary endpoint compared the efficacy of vilaprisan with placebo at 12 weeks, assessed as the absence of bleeding/spotting by bleeding diary. Secondary endpoints compared the efficacy of vilaprisan with ulipristal acetate. Results of the first 12-week treatment period are reported here. Results: Women (mean age 42.5 years) were enrolled from 1 June 2015. At baseline, mean menstrual blood loss per 28 days was 214.1 mL and the volume of the three largest UF was 106.2 mL. In total, 155 women completed the initial 12-week treatment period. Complete absence of bleeding/spotting until the end of the 12-week treatment period was achieved by 62.9 % of women receiving vilaprisan versus 0.0 % with placebo (p < .001); 55.4 % of women treated with ulipristal acetate reported absence of bleeding/spotting. The predefined HMB response (<80 mL and >50 % reduction from baseline during the last 28 days of treatment) was observed in 95.7 % of subjects treated with vilaprisan and 86.5 % of subjects treated with ulipristal acetate. Vilaprisan and ulipristal acetate treatment reduced the sum of the volume of the three largest UF by 29.9 % and 23.8 %, respectively, whereas an increase of 6.3 % was observed in the placebo group. No safety concerns, including multiple laboratory parameters, were identified. Conclusion: Daily administration of vilaprisan 2 mg induced amenorrhea, controlled bleeding, decreased UF size, and was well tolerated in women with HMB associated with UF. Clinical Trial Registration: ClinicalTrials.gov number: NCT02465814 https://clinicaltrials.gov/ct2/show/NCT02465814